LB-006 Quality Of Methods Reporting In Colitis Experiments And The Subsequent Impact On The Development Of A Gut Knowledge Base. (9th June 2014) - Bramhall, ML; Flórez-Vargas, O; Stevens, R; Wilson, J; Cruickshank, S; Brass, A
Abstract : Introduction: Current gastroenterological research generates vast quantities of clinical or animal model-derived data that is necessary to the study of IBD, yet much of it lies unused in repositories after publication. There is a growing need to develop more appropriate, structured storage systems that can be used by researchers to query this wealth of information with emerging questions. A domain-specific knowledge base combining clinical and laboratory datasets, annotated and connected via ontological terms, would be a valuable tool for gastroenterologists. However, development of a gut domain knowledge base may be severely impeded by incomplete methods reporting in the literature. This is further compounded by two factors. Firstly, non-domain experts, who may not be well suited to identifying missing methods, usually undertake construction of a knowledge base. Secondly, variations in experimental protocols may make it difficult for investigators to compare results from similar, but not identical, experiments. Methods: In order to address these issues we have systematically collated published papers that employed the widely used DSS colitis model. The papers were assessed against a checklist of essential parameters that should be reported for the experiment to be accurately described to allow for correct annotation and entry into a knowledge base. Results: We provide a comprehensive review of the quality of methods reporting in experiments using the DSS colitis model. We also report on the heterogeneity of the DSS colitis model currently in use. Conclusion: We provide a number of recommendations in order for researchers to standardise their methods and ensure that all relevant factors are reported during the publication of their research. Building from this, we will use what we have learnt to better inform the construction of a gut domain knowledge base. Disclosure of Interest: M. Bramhall Grant/research support from: Epistem Ltd., O. Flórez-Vargas: None Declared, R. Stevens: None Declared, J. Wilson: None Declared, S. Cruickshank: None Declared, A. Brass: None Declared.